Application of the Project-Based Learning Model Through Scrapbook Media to Increase Student Creativity in Class X at SMA Negeri 8 Pontianak - Alicia, Amanda; Asiri, Fadillah Rahmadani; Nur, Hafiz; Barella, Yusawinur; Sumantri, Sumantri; Fernanda Putri, Kezya Meylani (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study examines the effectiveness of implementing the Project Based Learning (PjBL) model using scrapbook media to enhance the creativity of 10th grade students at SMA Negeri 8 Pontianak. Creativity is an important aspect in the learning process because it encourages students to innovate and find new solutions to various problems. The research was conducted using a mixed method with a Concurrent Embedded design, where quantitative and qualitative data were collected simultaneously. Quantitative data were obtained through Quasi Experimental with Nonequivalent Control Group Design, while qualitative data were collected from observations, interviews, and documentation. The results showed an increase in creativity among students who participated in PjBL-based learning using scrapbooks. Independent T-Test analysis revealed a significant difference between the experimental and control classes. Qualitatively, the use of this model increased student engagement, critical thinking skills, cooperation, and creative expression during the learning process. Thus, the scrapbook-based PjBL model can be an innovative learning alternative for developing student creativity in schools.